Men’s perceptions about family planning - Shahaduzzaman (BRAC Research and Evaluation Division (RED), 2020)
This study looked at the men's perception on family planning, their knowledge and opinion about different contraceptives, as well as the motivating factors of the male for accepting family planning. Information was collected in December 1996 from Sherpur district through informal discussions, focus group discussions with men below and above the age of 40 years, religious leaders and with Garo ethnic group. Case histories of 6 condom users and 6 vasectomised clients were also taken. Men generally have a positive attitude towards family planning. They have definite ideas about optimal family size and own fertility, and also have a high knowledge on contraceptives. This knowledge mostly appeared to be superficial. Though there was a trace of the feeling in men that contraceptives were women's responsibility. Men were not properly by the programmes. Thus lack of information and under the influence of rumors their supportive and user roles were hampered. The perceived limitation of male contraceptive choice was also a major determinant of male contraceptive use. However, the male method users were gen;:rally satisfied with their methods. The depotholders of BRAC were found to be popular and well accepted by the male community, though their role was not properly known by men. Male forums and male contact were found to be inadequate. There was a gross misconception about the family planning registration card given by BRAC. To well publicize services and to promote the male contraceptives, to fulfill knowledge gap about BRAC's Family Planning Facilitation Programme by strengthening male forums were recommended.